Agrarian Law Reform in Indonesia: Between Legal Certainty and Social Justice - Eril Boli; Muh Nur Hidayat (Indonesian Civil Law Review, 2025)
Agrarian law reform in Indonesia is an important effort to regulate the control and use of land in line with the principles of legal certainty and social justice. The phenomenon of inequality in land distribution, overlapping land rights, and the spread of agrarian conflicts are the main challenges in realizing equitable agrarian reform. This study aims to analyze the dynamics of agrarian law reform in Indonesia since the enactment of Law Number 5 of 1960 concerning the Basic Regulations on Agrarian Principles (UUPA) through a normative juridical approach. Data is obtained from primary legal sources such as the UUPA, implementing regulations, court rulings, as well as relevant scientific literature and legal doctrine. The results of the study revealed that although the UUPA has become a comprehensive legal foundation, its implementation still faces various obstacles in ensuring legal certainty and social justice, especially related to agrarian conflicts and the protection of indigenous peoples' rights. A more responsive and inclusive legal approach is needed to address regulatory gaps and strengthen the protection of land rights for all levels of society. This study recommends policy reforms that integrate aspects of legal certainty and social justice through participatory dispute resolution mechanisms and formal recognition of indigenous peoples' rights in the national agrarian legal system.